Decoding communicative language teaching: Malaysian primary school teachers’ understanding, misconceptions, and lesson plans - Amirah Akhyar; Charanjit Kaur Swaran Singh; Tarsame Singh Mada Singh; Farkhodjon Rakhimjonov; Khusanova Nigina; Ulugbek Jabbarov (Universitas Syiah Kuala, 2026)
Despite the adoption of Communicative Language Teaching (CLT) for primary English education in Malaysia, a significant implementation gap persists between policy and classroom practice. Previous research has focused primarily on implementation outcomes rather than examining the underlying theoretical understanding that shapes pedagogical choices. Furthermore, limited studies have comprehensively documented the specific nature and extent of CLT misconceptions in the Malaysian context. This qualitative case study examines how six experienced primary school teachers in Selangor perceive CLT principles, the misconceptions they hold, and how these factors impact their lesson planning. Data collection included classroom observations, lesson plan analysis, and semi-structured interviews. The findings reveal that teachers’ understanding of CLT often emphasizes speaking activities and group work while overlooking authentic communication and learner autonomy. Common misconceptions included beliefs that CLT requires abandoning grammar instruction, is only suitable for high-proficiency students, and necessitates group work. Analysis revealed a significant gap between teachers’ stated understanding and actual planning practices, with many reverting to traditional, teacher-centered activities despite expressing support for communicative approaches. Contextual factors, including examination pressure, large class sizes, and limited resources, further constrained implementation. These findings highlight the need for comprehensive teacher training that addresses both theoretical foundations and practical implementation of CLT within the Malaysian primary school context while considering local cultural and institutional constraints.